Effects of Repeated Ethanol Exposures on NMDA Receptor Expression and Locomotor Sensitization in Mice Expressing Ethanol Resistant NMDA Receptors - den Hartog, Carolina R.; Gilstrap, Meghin; Eaton, Bethany; Lench, Daniel H.; Mulholland, Patrick J.; Homanics, Gregg. E.; Woodward, John J. (Frontiers in Neuroscience, 2017)
Evidence from a large number of preclinical studies suggests that chronic exposure to drugs of abuse such as psychostimulants or ethanol induces changes in glutamatergic transmission in key brain areas associated with reward and control of behavior. These changes include alterations in the expression of ionotropic glutamate receptors including N-methyl-D-aspartate receptors (NMDAR) that are important for regulating neuronal activity and synaptic plasticity. NMDA receptors are inhibited by ethanol and reductions in NMDA-mediated signaling are thought to trigger homestatic responses that limit ethanol’s effects on glutamatergic transmission. Following repeated exposures to ethanol, these homeostatic responses may become unstable leading to an altered glutamatergic state that contributes to the escalations in drinking and cognitive deficits observed in alcohol-dependent subjects. An important unanswered question is whether ethanol-induced changes in NMDAR expression are modulated by the intrinsic sensitivity of the receptor to ethanol. In this study, we examined the effects of ethanol on NMDAR subunit expression in cortical (orbitofrontal, medial prefrontal), striatal (dorsal and ventral striatum) and limbic (dorsal hippocampus, basolateral amygdala) areas in mice genetically modified to express ethanol-resistant receptors (F639A mice). These mice have been previously shown to drink more ethanol than their wild-type counterparts and have altered behavioral responses to certain actions of ethanol. Following long-term voluntary drinking, F639A mice showed elevations in GluN2A but not GluN1 or GluN2B expression as compared to wild-type mice. Mice treated with repeated injections with ethanol (2-3.5 g/kg; i.p.) showed changes in NMDAR expression that varied in a complex manner with genotype, brain region, subunit type and exposure protocol all contributing to the observed response. F639A mice, but not wild-type mice, showed enhanced motor activity following repeated ethanol injections and this was associated with differences in NMDAR subunit expression across brain regions thought to be involved in drug sensitization. Overall, while the results of the study suggest that NMDARs with reduced sensitivity to ethanol favor the development of locomotor sensitization, they also show that intrinsic ethanol sensitivity is not the sole determinant underlying changes in NMDAR expression following repeated exposures to ethanol.